2018
DOI: 10.1016/j.addma.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of layer thickness and post-process treatments on the fatigue properties of CoCr scaffolds produced by laser powder bed fusion

Abstract: Over the last years, additive manufacturing (AM) techniques such as laser powder bed fusion (L-PBF) have been frequently adopted for efficiently producing biomedical implants. L-PBF offers the advantage of low material waste and high accuracy enabling the production of complex and highly personalized geometries. However, when manufacturing time is considered, the L-PBF production rate is relatively low compared to conventional production techniques. The aim of this paper is to present the impact of layer thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…On the other hand, Cutolo et al [100] reported an increase of the fatigue performances of chemically etched CoCr samples on a local scale (Fig. 8), while the HIP treatment seemed to be ineffective.…”
Section: Fatigue Testmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, Cutolo et al [100] reported an increase of the fatigue performances of chemically etched CoCr samples on a local scale (Fig. 8), while the HIP treatment seemed to be ineffective.…”
Section: Fatigue Testmentioning
confidence: 93%
“…Heat treatment and chemical etching have been studied to reduce these issues. Many scientists [98][99][100][101] found that a heat treatment reduces the strength of the samples and increases the ductility. On the other hand, Van Hooreweder et al [102] reported that chemical etching has no influence on mechanical properties while, in another paper, Van Hooreweder et al [103] found that the different densities of the samples have a strong influence on the mechanical properties making the study of the heat treatment and chemical etching effects hard.…”
Section: Compression Testsmentioning
confidence: 99%
“…Among bioinert metals, the titanium alloy Ti-6Al-4V, 109,115,153,158,170,178,179 Co-Cr alloys, 180,181 pure titanium, 182,183 stainless steel, 174,184 NiTi alloys, [185][186][187][188] and tantalum 189 are the most important biomaterials used for fabrication of AM porous structures. Ti-6Al-4V is probably the most extensively studied material given its high mechanical properties, good biocompatibility, relatively low price, and widely available experience regarding its processing with AM.…”
Section: Bioinert Metals and Alloysmentioning
confidence: 99%
“…Once more, the best design of these post-AM processes and their applicability to different materials are not yet well understood. As a consequence, HIP treatments are not always successful in improving the mechanical behaviour of AM metals [ 50 , 51 ]. Further research is therefore needed to clarify what the best post-treatments are for every type of material and geometrical design.…”
Section: Post-am Treatmentsmentioning
confidence: 99%
“…For more complex parts, it is either expensive or infeasible to perform machining or polishing in which case (electro) chemical surface treatments could be helpful in smoothening the surface of AM parts. It has been shown that a treatment improving the surface of AM metals may significantly improve their fatigue performance [ 50 ]. However, further investigation is called for to determine what the most effective types of treatments are and to integrate those post-AM processes into the production line of AM metals.…”
Section: Post-am Treatmentsmentioning
confidence: 99%